2022
DOI: 10.3389/fbioe.2022.899157
|View full text |Cite
|
Sign up to set email alerts
|

α-Hemihydrate calcium sulfate/n-hydroxyapatite combined with metformin promotes osteogenesis in vitro and in vivo

Abstract: This study aimed to examine the effects of loading different concentrations of metformin onto an α-hemihydrate calcium sulfate/nano-hydroxyapatite (α-CSH/nHA) composite. The material characteristics, biocompatibility, and bone formation were compared as functions of the metformin concentration. X-ray diffraction results indicated that the metformin loading had little influence on the phase composition of the composite. The hemolytic potential of the composite was found to be low, and a CCK-8 assay revealed onl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Such injectable CP gels are prepared from powders and liquid components that form a paste that can be injected into a bone defect in situ upon mixing [9]. In modern practice, injectable CPs are synthesized using a combination of rapidly and slightly resorbable calcium phosphates, such as calcium sulfate and hydroxyapatite in a resorbable polymer gel [10,12,13,20].…”
Section: Introductionmentioning
confidence: 99%
“…Such injectable CP gels are prepared from powders and liquid components that form a paste that can be injected into a bone defect in situ upon mixing [9]. In modern practice, injectable CPs are synthesized using a combination of rapidly and slightly resorbable calcium phosphates, such as calcium sulfate and hydroxyapatite in a resorbable polymer gel [10,12,13,20].…”
Section: Introductionmentioning
confidence: 99%
“…Others reported that 500 μM metformin has the strongest effect on osteogenesis, and 250 and 1,000 μM metformin have some increased osteogenic potential compared to the control, but the effect is weaker compared to that of 500 μM metformin. To stimulate bone formation, a stable metformin concentration is essential ( Liu et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%